(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This work is about the design and construction of an RFID based electronic attendance register. It takes advantage of the wireless and cheap RFID technology. It is microcontroller based and the Arduino Micro-controller was used as well as the MFRC522 RFID module. Each subject of the register would be represented by a tag whose identity is already stored, which when placed close to the reader would cause the micro-controller to log the subject’s information in LCD. The stages involved in this research are the design stage where the whole system was designed, the coding stage where the code for the microcontroller was written and debugged and the final build stage where everything was put together. This system can be used to take attendance for student in school, college, and university. It also can be used to take attendance for workers in working places. Its ability to uniquely identify each person based on their RFID tag type of ID card make the process of taking the attendance easier, faster and secure as compared to conventional method. Students or workers only need to place their ID card on the reader and their attendance will be taken immediately. With real time clock capability of the system, attendance taken will be more accurate since the time for the attendance taken will be recorded